Antidepressant-Like and Anxiolytic-Like Effects of Cannabidiol: A Chemical Compound of Cannabis sativa - R. de Mello Schier, Alexandre; P. de Oliveira Ribeiro, Natalia; S. Coutinho, Danielle; Machado, Sergio; Arias-Carrion, Oscar; A. Crippa, Jose; W. Zuardi, Antonio; E. Nardi, Antonio; C. Silva, Adriana (CNS & Neurological Disorders - Drug Targets, 2014)
Anxiety and depression are pathologies that affect human beings in many aspects of life, including social life, productivity and health. Cannabidiol (CBD) is a constituent non-psychotomimetic of Cannabis sativa with great psychiatric potential, including uses as an antidepressant-like and anxiolytic-like compound. The aim of this study is to review studies of animal models using CBD as an anxiolytic-like and antidepressant-like compound. Studies involving animal models, performing a variety of experiments on the above-mentioned disorders, such as the forced swimming test (FST), elevated plus maze (EPM) and Vogel conflict test (VCT), suggest that CBD exhibited an anti-anxiety and antidepressant effects in animal models discussed. Experiments with CBD demonstrated non-activation of neuroreceptors CB1 and CB2. Most of the studies demonstrated a good interaction between CBD and the 5-HT1A neuro-receptor.
Keywords: anxiolytic-like